A conceptual model to facilitate transitions from primary care to specialty substance use disorder care: a review of the literature. Issue 5 (12th May 2014) - Cucciare, Michael A.; Coleman, Eric A.; Timko, Christine
<x content-type="archive" xml:space="preserve">Abstract</x> Aim This article presents a conceptual model to help facilitate the transition from primary care to specialty substance use disorder (SUD) care for appropriate patients. Background Substance misuse is a common health condition among patients presenting to primary care settings and may complicate the treatment of chronic health conditions such as diabetes and hypertension. It is therefore critical that primary care providers be prepared to identify and determine appropriate treatment options for patients presenting with substance misuse. Methods We conducted a narrative review that occurred in three stages: literature review of health care transition models, identification of conceptual domains common across care transition models, and identification of SUD-specific model elements. Findings The conceptual model presented describes patient, provider, and system-level facilitators and barriers to the transition process, and includes intervention strategies that can be utilized by primary care clinics to potentially improve the process of transitioning patients from primary care to SUD care. Recognizing that primary care clinics vary in available resources, we present three examples of care practices along an intensity continuum from low (counseling and referral) to moderate (telephone monitoring) to high (intensive case management) resource demands for adoption. We also provide a list of common outcomes clinics might consider when evaluating the impact of care transition practices in this patient population; these include process outcomes such as patients' increased knowledge of available treatment resources, and health outcomes such as patients' reduced substance use and better quality of life.